Comparison of motor skill learning, grip strength and memory recall on land and in chest-deep water - Bressel, Eadric; Vakula, Michael N.; Kim, Youngwook; Bolton, David A. E.; Dakin, Christopher J. (PLOS ONE, 2018)
Immersion in chest-deep water may augment explicit memory in healthy adults however, there is limited information on how this environment might affect implicit memory or motor learning. The purpose of this study was to compare the speed and accuracy for learning a motor skill on land and in chest-deep water. Verbal word recall and grip strength were included to gain a more complete understanding of the intervention. Sixty-two younger adults (age = 23.3 ± 3.59 yrs.) were randomly assigned to either a water group immersed to the xiphoid or a land group. Participants in both groups completed the same eight practice trials of a mirror-drawing task on two separate days. Outcome measures for this task included time and error numbers to complete each drawing. The number of words recalled using a 12 word recall test, and peak grip strength using a hand dynamometer were measured each day of testing. The influence of environment and repeated practice on each outcome measure were assessed with an analysis of variance and effect sizes (ES). Time and errors for both groups significantly decreased with practice (p < 0.01, ES = 0.11–0.28), however the drawing time was greater in water than on land for trials 1, 5, and 6 (ES = 0.50–0.55). There was a 7% increase in words recalled (9.24 ± 1.19 vs 8.60 ± 1.19) and a 16% increase in grip strength (405 ± 104 vs 342 ± 83) for water than land groups (ES 0.54–0.64). Healthy adults in chest-deep water and on land display comparable mirror-drawing speed and accuracy after minimal practice. Curiously, water immersion may augment verbal word recall and grip strength abilities.